Contrasted geomorphological and limnological properties of thermokarst lakes formed in buried glacier ice and ice-wedge polygon terrain - Coulombe, Stéphanie; Fortier, Daniel; Bouchard, Frédéric; Paquette, Michel; Charbonneau, Simon; Lacelle, Denis; Laurion, Isabelle; Pienitz, Reinhard (The Cryosphere, 2022)
In formerly glaciated permafrost regions, extensive areas are still underlain by a considerable amount of glacier ice buried by glacigenic sediments. It is expected that large parts of glacier ice buried in the permafrost will melt in the near future, although the intensity and timing will depend on local terrain conditions and the magnitude and rate of future climate trends in different Arctic regions. The impact of these ice bodies on landscape evolution remains uncertain since the extent and volume of undisturbed relict glacier ice are unknown. These remnants of glacier ice buried and preserved in the permafrost contribute to the high spatial variability in ground ice condition of these landscapes, leading to the formation of lakes with diverse origins and morphometric and limnological properties. This study focuses on thermokarst lake initiation and development in response to varying ground ice conditions in a glacial valley on Bylot Island (Nunavut). We studied a lake-rich area using lake sediment cores, detailed bathymetric data, remotely sensed data and observations of buried glacier ice exposures. Our results suggest that initiation of thermokarst lakes in the valley was triggered from the melting of either buried glacier ice or intrasedimental ice and ice wedges. Over time, all lakes enlarged through thermal and mechanical shoreline erosion, as well as vertically through thaw consolidation and subsidence. Some of them coalesced with neighbouring water bodies to develop larger lakes. These glacial thermokarst lakes formed in buried glacier ice now evolve as “classic” thermokarst lakes that expand in area and volume as a result of the melting of intrasedimental ground ice in the surrounding material and the underlying glaciofluvial and till material. It is expected that the deepening of thaw bulbs (taliks) and the enlargement of Arctic lakes in response to global warming will reach undisturbed buried glacier ice where it is still present, which in turn will substantially alter lake bathymetry, ...